Morphological neurite changes induced by porcupine inhibition are rescued by Wnt ligands - Godoy, Juan A.; Espinoza-Caicedo, Jasson; Inestrosa, Nibaldo C. (My University, 2021)
Background: Wnt signaling plays key roles in cellular and physiological processes, including cell proliferation, differentiation and migration during development and tissue homeostasis in adults. This pathway can be defined as Wnt/beta-catenin-dependent or beta-catenin-independent or "non-canonical", both signaling are involved in neurite and synapse development/maintenance. Porcupine (PORCN), an acylase that o-acylates Wnt ligands, a major modification in secretion and interaction with its receptors. We use Wnt-C59, a specific PORCN inhibitor, to block the secretion of endogenous Wnts in embryonic hippocampal neurons (DIV 4). Under these conditions, the activity of exogenous Wnt ligands on the complexity of the dendritic tree and axonal polarity were evaluated Methods: Cultured primary embryonic hippocampal neurons obtained from Sprague-Dawley rat fetuses (E18), were cultured until day in vitro (DIV) 4 (according to Banker ' s protocol) and treated with Wnt-C59 for 24 h, Wnt ligands were added to the cultures on DIV 3 for 24 h. Dendritic arbors and neurites were analysis by fluorescence microscopy. Transfection with Lipofectamine 2000 on DIV 2 of plasmid expressing eGFP and KIF5-Cherry was carried out to evaluate neuronal polarity. Immunostaining was performed with MAP1B and Tau protein. Immunoblot analysis was carried out with Wnt3a, beta-catenin and GSK-3 beta (p-Ser9). Quantitative analysis of dendrite morphology was carried out with ImageJ (NIH) software with Neuron J Plugin. Results: We report, here, that Wnt-C59 treatment changed the morphology of the dendritic arbors and neurites of embryonic hippocampal neurons, with decreases beta-catenin and Wnt3a and an apparent increase in GSK-3 beta (p-Ser9) levels. No effect was observed on axonal polarity. In sister cultures, addition of exogenous Wnt3a, 5a and 7a ligands rescued the changes in neuronal morphology. Wnt3a restored the length of neurites to near that of the control, but Wnt7a increased the neurite length beyond that of the control. Wnt5a also restored the length of neurites relative to Wnt concentrations. Conclusions: Results indicated that Wnt ligands, added exogenously, restored dendritic arbor complexity in embryonic hippocampal neurons, previously treated with a high affinity specific Porcupine inhibitor. We proposed that PORCN is an emerging molecular target of interest in the search for preclinical options to study and treat Wnt-related diseases.
Keywords: wnt signaling; porcupine; neurites; dendritic arbor complexity; embryonic hippocampal neurons